Future Gaming Creative Interventions in Video Game Culture - Ruffino, Paolo (Future Media, 2018)
This book is not about the future of video games. It is not an attempt to predict the moods of the market, the changing profile of gamers, the benevolence or malevolence of the medium. There are sufficient bodies dedicated to those predictions - and this book is about them. It is about the ways in which the past, present and future notion of games are narrated and negotiated by a small group of producers, journalists, and gamers, and about how invested these narrators are in telling the story of tomorrow.